2018
DOI: 10.15408/etk.v17i1.6711
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Soundness Level of Islamic Banks in Indonesia and Malaysia

Abstract: This study was conducted to analyze the soundness comparison of Islamic banks in Indonesia and Malaysia to measure the readiness of Islamic banks in both countries In facing of financial integration in the ASEAN Economic Community (AEC) by 2020. The study uses data of annual financial statements in 10 Islamic banks in each country in period 2012-2014 using CAMEL Method. The results of this study indicate that Islamic banks in Malaysia are relatively better prepared compared to Islamic banks in Indonesia. Islam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The findings of a recent study (Hosen & Muhari, 2018) indicate that the state of Islamic financial institutions in Indonesia and Islamic financial institutions in Malaysia are not same. According to the findings of a study (Chabachib et al, 2019) Islamic banks in Indonesia and Islamic banks in Malaysia are very different from one another in a number of significant ways.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The findings of a recent study (Hosen & Muhari, 2018) indicate that the state of Islamic financial institutions in Indonesia and Islamic financial institutions in Malaysia are not same. According to the findings of a study (Chabachib et al, 2019) Islamic banks in Indonesia and Islamic banks in Malaysia are very different from one another in a number of significant ways.…”
Section: Introductionmentioning
confidence: 92%
“…Research result (Hosen & Muhari, 2018) demonstrates that the financial state of Islamic banks in Malaysia and Islamic banks in Indonesia are in quite different places right now. Study (Chabachib et al, 2019) found out that there are significant distinctions between Islamic financial institutions in Malaysia and Islamic financial institutions in Indonesia.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, there was no correlation between firm ownership and ROE and ROA. Hosen & Fitria (2018) studied the relationship between the concentration ratio of the four largest Islamic commercial banks (BUS) and Islamic Rural Banks' performance in Indonesia from 2010-2015. The findings indicate that BUS, Islamic Banking Subsidiary (UUS), and BPRS competed for the same Micro, Small, and Medium-Sized Enterprises (MSME) and Murabaha sectors.…”
Section: Indonesian Ib Performance (Cluster 2 -Market Concentration)mentioning
confidence: 99%
“…Hal ini dapat digunakan untuk melihat seberapa efektif metode RGEC dalam menilai kesehatan bank. Terakhir, berbeda dengan penelitian Hosen & Muhari 16 yang meneliti beberapa Bank Umum Syariah, sedangkan penelitian ini menggunakan seluruh BUS yang beroperasi di Indonesia sebagai sampel penelitian. Dengan menggunakan sampel seluruh BUS di Indonesia maka akan didapatkan hasil yang lebih mencerminkan kondisi kesehatan bank secara keseluruhan.…”
Section: Sumber: Otoritas Jasa Keuangan (2020) Diolah Penulisunclassified